Territorial organization for ecotourism development in Hoang Lien National Park, Sapa District, Lao Cai Province - Hai, Nguyen Thi; Quy Hoi, Nguyen Thi; Mai Hoa, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences, 2008)
Abstract